2018
DOI: 10.2147/ijn.s182621
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anticancer activity and intracellular uptake of paclitaxel-containing solid lipid nanoparticles in multidrug-resistant breast cancer cells

Abstract: PurposeThe aim of this study was to show enhanced anticancer activity of paclitaxel (Ptx) incorporated into solid lipid nanoparticles (SLNs) and reveal reversal of multidrug resistance (MDR) by SLNs mediated by increased uptake through different entry mechanisms from that in drug-sensitive cells.MethodsAnticancer activity of Ptx incorporated in SLNs (Ptx-SLNs) was measured in the drug-sensitive human breast cancer cell line MCF7 and its MDR variant MCF7/ADR. Cellular uptake of cargo molecules in SLNs was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…All in all, there are many drugs that have been incorporated in SLNs with positive results [30,59,60,61,62,63,64], as well as tumors in which their action has been verified [58,63,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80]. These are the main supports for the advance in research on the use of SLNs in tumor treatments.…”
Section: Critical Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…All in all, there are many drugs that have been incorporated in SLNs with positive results [30,59,60,61,62,63,64], as well as tumors in which their action has been verified [58,63,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80]. These are the main supports for the advance in research on the use of SLNs in tumor treatments.…”
Section: Critical Discussion and Future Perspectivesmentioning
confidence: 99%
“…The evaluation of concentration-dependent cytotoxicity indicated that SLNs with paclitaxel notably improved the IC 50 concentration in drug-resistant cells. Besides, these nanocarriers provided an enhanced cellular uptake in relation to the other formulations especially in drug-resistant cells, proving that SLNs are effective in avoiding multidrug resistance mechanisms in breast cancer cells [66].…”
Section: Effective Use Of Slns In Different Types Of Tumorsmentioning
confidence: 99%
“… 98 Likewise, Rhodamine 123-loaded SLNPs (average diameter 224 nm) were taken up by multidrug-resistant breast cancer cells by endocytosis. 99 The nano-scaled size, generally spherical shape and negative surface charge might have contributed to the internalization of SLNPs. 100 …”
Section: Discussionmentioning
confidence: 99%
“…Xu et al significantly enhanced the anti-cancer activity of PTX by incorporating it into solid lipid nanoparticles in MCF7 and MCF7/ADR cell lines. Encapsulation of PTX into solid lipid nanoparticles successfully reversed the multidrug resistance by evading the efflux pumps in drug-resistant cells [ 179 ]. In addition to these formulations, co-encapsulation of PTX with other drugs into nano-formulations significantly enhanced the anti-cancer activity of the compounds in metastatic/multidrug-resistant breast cancer cells.…”
Section: Nanomedicine To Overcome Drug Resistance In Breast Cancermentioning
confidence: 99%